An Examination of Exchange Rates on Foreign Tourist Flows into ASEAN-3 - Purna, Fitra Prasapawidya; Munandar, Aris; Bija, Rein Pong (Universitas Negeri Semarang, 2021)
This research aims to analyze the effect of exchange rates on foreign tourist flows in ASEAN-3. A fixed-effect model is used to estimate data from three ASEAN countries, namely: Indonesia, Malaysia, and Thailand from 1995 to 2016. The result shows that the exchange rate has a significant positive effect on foreign tourist flow. In other words, the depreciation of domestic currency increasing foreign tourist flow. Other control variables such as income per capita, HIV prevalence, trade, and consumer price index significantly affect a different sign.